From OPIMA to MPEG IPMP-X: A standard's history across R&D projects - Serrão, C.; Dias, J.; Kudumakis, P. (Signal Processing: Image Communication, 2005)
This paper describes the work performed by a number of companies and universities who have been working as a consortium under the umbrella of the European Union Framework Programme 5 (FP5), Information Society Technologies (IST) research program, in order to provide a set of Digital Rights Management (DRM) technologies and architectures, aiming at helping to reduce the copyright circumvention risks, that have been threatening the music and film industries in their transition from the “analogue” to “digital” age. The paper starts by addressing some of the earlier standardization efforts in the DRM arena, namely, Open Platform Initiative for Multimedia Access (OPIMA). One of the described FP5 IST projects, Open Components for Controlled Access to Multimedia Material (OCCAMM), has developed the OPIMA vision. The paper addresses also the Motion Pictures Expert Group—MPEG DRM work, starting from the MPEG Intellectual Propriety Management and Protection—IPMP “Hooks”, towards the MPEG IPMP Extensions, which has originated the first DRM-related standard (MPEG-4 Part 13, called IPMP Extensions or IPMP-X) ever released by ISO up to the present days.2 The paper clarifies how the FP5 IST project MPEG Open Security for Embedded Systems (MOSES), has extended the OPIMA interfaces and architecture to achieve compliance with the MPEG IPMP-X standard, and how it has contributed to the achievement of “consensus” and to the specification, implementation (Reference Software) and validation (Conformance Testing) of the MPEG IPMP-X standard.